Ciguatoxin enhances quantal transmitter release from frog motor nerve terminals. - Molgó, J. (1990)
1. Ciguatoxin (CTX), a marine toxin produced by the benthic dinoflagellate Gambierdiscus toxicus, is responsible for a complex endemic disease in man known as ciguatera fish poisoning. In the present study we have investigated the effects of purified CTX extracted for Gymnothorax javanicus moray-eel liver on frog isolated neuromuscular preparations with conventional electrophysiological techniques. 2. CTX (1-2.5 nM) applied to cutaneous pectoris nerve-muscle preparations induced, after a short delay, spontaneous fibrillations of the muscle fibres that could be suppressed with 1 microM tetrodotoxin (TTX) or by formamide to uncouple excitation-contraction. 3. In preparations treated with formamide, CTX (1-2.5 nM) caused either spontaneous or repetitive muscle action potentials (up to frequencies of 60-100 Hz) in response to a single nerve stimulus. Recordings performed at extrajunctional regions of the muscle membrane revealed that during the repetitive firing a prolongation of the repolarizing phase of the action potential occurred. At junctional sites the repetitive action potentials were triggered by repetitive endplate potentials (e.p.ps). 4. CTX (2.5 nM) caused a TTX-sensitive depolarization of the muscle membrane. 5. In junctions equilibrated in solutions containing high Mg2+ + low Ca2+, addition of CTX (1.5 nM) first induced an average increase of 239 +/- 36% in the mean quantal content of e.p.ps. Subsequently CTX reduced and finally blocked nerve-evoked transmitter release irreversibly. 6. CTX (1.5-2.5 nM) increased the frequency of miniature endplate potentials (m.e.p.ps) in junctions bathed either in normal Ringer, low Ca2(+)-high Mg2+ medium or in a nominally Ca2(+)-free solution containing EGTA.2+ Extensive washing with toxin-free solutions did not reverse the effect.(ABSTRACT TRUNCATED AT 250 WORDS)